Human rights violations among sexual and gender minorities in Kathmandu, Nepal: a qualitative investigation - Singh Sonal; Pant Sunil; Dhakal Suben; Pokhrel Subash; Mullany Luke C (BMC, 2012)
Abstract Background Nepal has experienced sporadic reports of human rights violations among sexual and gender minorities. Our objective was to identify a range of human rights that are enshrined in international law and/or are commonly reported by sexual and gender minority participants in Kathmandu, to be nonprotected or violated. Methods In September 2009 three focus group discussions were conducted by trained interviewers among a convenience sample of sexual and gender minority participants in Kathmandu Nepal. The modified Delphi technique was utilized to elicit and rank participant-generated definitions of human rights and their subsequent violations. Data was analyzed independently and cross checked by another investigator. Results Participants (n = 29) reported experiencing a range of human rights violations at home, work, educational, health care settings and in public places. Lack of adequate legal protection, physical and mental abuse and torture were commonly reported. Access to adequate legal protection and improvements in the family and healthcare environment were ranked as the most important priority areas. Conclusions Sexual and gender minorities in Nepal experienced a range of human rights violations. Future efforts should enroll a larger and more systematic sample of participants to determine frequency, timing, and/or intensity of exposure to rights violations, and estimate the population-based impact of these rights violations on specific health outcomes